Negative impact of the pandemic on hospital admissions, morbidity and early mortality for acute cirrhosis decompensation. Issue 1 (17th January 2023) - Gananandan, Kohilan; Phillips, Alexandra; Chikhlia, Anmol; Old, Hannah; Sim, Sharmaine Jia Ying; Thakur, Niharika; Hussain, Ishrat; Kazankov, Konstantin; Mookerjee, Rajeshwar P
Abstract : Introduction: The global pandemic has diverted resources away from management of chronic diseases, including cirrhosis. While there is increasing knowledge on COVID-19 infection in liver cirrhosis, little is described on the impact of the pandemic on decompensated cirrhosis admissions and outcomes, which was the aim of this study. Methods: A single-centre, retrospective study, evaluated decompensated cirrhosis admissions to a tertiary London hepatology and transplantation centre, from October 2018 to February 2021. Patients were included if they had an admission with cirrhosis decompensation defined as new-onset jaundice or ascites, infection, encephalopathy, portal hypertensive bleeding or renal dysfunction. Results: The average number of admissions stayed constant between the pre-COVID-19 (October 2018–February 2020) and COVID-19 periods (March 2020–February 2021). Patients transferred in from secondary centres had consistently higher severity scores during the COVID-19 period (UK Model for End-Stage Liver Disease 58 vs 54; p=0.007, Model for End-Stage Liver Disease-Sodium 22 vs 18; p=0.006, EF-CLIF Acute Decompensation (AD) score 55.0 vs 51.0; p=0.055). Of those admitted to the intensive care without acute-on-chronic liver failure, there was a significant increase in AD scores during the COVID-19 period (58 vs 48, p=0.009). In addition, there was a trend towards increased hospital readmission rates during the COVID-19 period (29.5% vs 21.5%, p=0.067). When censored at 30 days, early mortality postdischarge was significantly higher during the COVID-19 period (p<0.001) with a median time to death of 35 days compared with 62 days pre-COVID-19. Discussion: This study provides a unique perspective on the impact that the global pandemic had on decompensated cirrhosis admissions. The findings of increased early mortality and readmissions, and higher AD scores on ICU admission, highlight the need to maintain resourcing for high-level hepatology care and follow-up, in spite of other disease pressures.